CHARACTERIZATION OF ENDOPHYTIC BACILLUS ISOLATED FROM SHALLOT ROOT AS BIOCONTROL OF BACTERIAL LEAF BLIGHT DISEASE - Resti, Zurai; Habazar, Trimurti; Putra, Deddi Prima; ., Nasrun (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Characterization of Endophytic Bacillus Isolated from Shallot Root as Biocontrol of Bacterial Leaf Blight Disease. Endophytic Bacillus isolated from the roots of healthy shallots has potential as biological control agent of bacterial leaf blight (BLB) disease. Based on the in planta screening, four endophytic bacteria that capable of controlling BLB diseases from the group of Bacillus were obtained, such as Bacillus cereus P14, Bacillus cereus Se07, Bacillus sp. HI, and Bacillus sp. SJI. The aims of this study were to investigate the characteristics of endophytic Bacillus that capable of controlling BLB disease and to determine the characteristic that most responsible in the disease control. This study method was descriptive. The characteristics observed were production of antibiotics by paper disc method, production of salicylic acid by capillary electrophoresis, and root colonization by in planta method. Linear regression analysis was used to determine the characteristic most responsible in the disease control. The results showed that four endophytic Bacillus were capable of producing salicylic acid and colonizing the root, and three of them were also capable of producing antibiotic. Salicylic acid production varied ranging from 13.96 to 14.72 ppm mL-1. Three endophytic Bacillus were capable of producing antibiotic with inhibition zone of 16.25 to 20.25 mm. Endophytic Bacillus was able to colonize the shallot roots with a population of bacteria ranged from 3.20 × 105-6, 20 × 105 CFU g-1 root. Based on the correlation coefficient of linear regression analysis, the root colonization of endophytic bacteria played the role in decreasing BLB disease.